An Economic Study on the Production and Consumption of Honey in the World and Libya during the Period (1985–2004) (Journal of human and social sciences, 2016)
This study examines the trends in production and consumption of honey worldwide and in Libya during the period 1985–2004. The research aims to identify the economic importance of honey as an agricultural product, assess the patterns of supply and demand, and highlight the factors influencing production levels and consumer behavior. Using available statistical data from international and national sources, the study compares global developments in honey production with those observed in Libya, analyzing changes in output, imports, exports, and per capita consumption. The results indicate a general increase in global honey production accompanied by rising consumption, driven by both nutritional and medicinal demand. In Libya, however, production growth was relatively modest and often insufficient to meet local needs, leading to reliance on imports. The study concludes by emphasizing the role of supportive agricultural policies, improved beekeeping practices, and investment in biotechnology to enhance local production and reduce dependence on foreign markets. These findings may contribute to shaping strategies for sustainable development in the apiculture sector in Libya and the wider region.
Keywords: Honey Production; Honey Consumption; Beekeeping; Economic Importance; Libya